2003
DOI: 10.1007/s00261-002-0059-6
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Bard Memotherm self-expanding metal stent in the palliation of colonic obstruction

Abstract: In our experience, the Memotherm Colorectal SEMS was easy to use, was effective in the palliation of obstructing colorectal carcinoma, and appeared to reduce the risk of stent migration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…Technical success in this series of colorectal stenting was achieved in 89% of patients and is comparable with that of other studies [7,16–18]. The technical failures resulted from an inability to manoeuvre the guidewire past the irregular lumen of the obstructing lesion in two thirds of patients, with vascular catheter slippage accounting for the remainder.…”
Section: Discussionsupporting
confidence: 80%
“…Technical success in this series of colorectal stenting was achieved in 89% of patients and is comparable with that of other studies [7,16–18]. The technical failures resulted from an inability to manoeuvre the guidewire past the irregular lumen of the obstructing lesion in two thirds of patients, with vascular catheter slippage accounting for the remainder.…”
Section: Discussionsupporting
confidence: 80%
“…However, most references are related to carcinomas of the left hemicolon and small groups of patients [3,12,15,17,18,[20][21][22]. In addition, most patients in the reports underwent SEMS implantation before a definitive surgical treatment (''bridge to surgery'' concept) for acute colorectal obstruction [23][24][25], or there were mixed groups of patients [18,26,27], leading to only limited conclusions on the long-term effect of SEMS implantation as definitive palliative treatment for obstructing colorectal carcinoma.…”
Section: Discussionmentioning
confidence: 98%
“…Several studies reported that the rate of stent migration is 4% to 10%. 5 , 15 , 23 This most frequently occurs within the first 24 hours; however, migration at 3 and 7 days after the procedure has been reported by Canon et al 21 Stent migration occurs because of technical factors such as inadequate expansion. In addition, the smaller the stent diameter, the more the colon is angulated; also, the more insufficient the length is to allow stent flaring, the easier could stent migration occur.…”
Section: Complicationsmentioning
confidence: 98%